![if \: 1 + {sin}^{2}\theta \: = 3sin\theta\times cos \theta \: \: \\ then \: prove \: that \: tan \theta \: = 1 \: or \: tan \theta = \frac{1}{2} if \: 1 + {sin}^{2}\theta \: = 3sin\theta\times cos \theta \: \: \\ then \: prove \: that \: tan \theta \: = 1 \: or \: tan \theta = \frac{1}{2}](https://tex.z-dn.net/?f=if+%5C%3A+1+%2B++%7Bsin%7D%5E%7B2%7D%5Ctheta+%5C%3A++%3D+3sin%5Ctheta%5Ctimes+cos+%5Ctheta+%5C%3A++%5C%3A++%5C%5C+then+%5C%3A+prove+%5C%3A+that+%5C%3A+tan+%5Ctheta+%5C%3A++%3D+1+%5C%3A+or+%5C%3A+tan+%5Ctheta+%3D++%5Cfrac%7B1%7D%7B2%7D+)
please answer don't spam or you will lose ur point
Answers
Answered by
7
Given: 1+sin2 θ = 3 sin θ cos θ Dividing L.H.S and R.H.S equations with sin2 θ, We get, cosec2 θ + 1 = 3 cot θ Since, cosec2 θ – cot2 θ = 1 ⇒ cosec2 θ = cot2 θ +1 ⇒ cot2 θ +1+1 = 3 cot θ ⇒ cot2 θ +2 = 3 cot θ ⇒ cot2 θ –3 cot θ +2 = 0 Splitting the middle term and then solving the equation, ⇒ cot2 θ – cot θ –2 cot θ +2 = 0 ⇒ cot θ(cot θ -1)–2(cot θ +1) = 0 ⇒ (cot θ – 1)(cot θ – 2) = 0 ⇒ cot θ = 1, 2 Since, tan θ = 1/cot θ tan θ = 1, ½ Hence, proved.Read more on Sarthaks.com - https://www.sarthaks.com/884852/if-1-sin-2-3sin-cos-then-prove-that-tan-1-or
Similar questions